DESCRIPTION OF EXAMINATION RESULTS FOR SYPHILIS / TP FAST IN PREGNANT WOMEN AT HEALTH CENTER, KOTA UTARA (Journal of Health, Technology and Science (JHTS), 2023)
The purpose of this study is to screen pregnant women at the North City Health Center for syphilis using a rapid method and to assess pregnant women's knowledge about syphilis using a questionnaire.This study used descriptive qualitative approach. The data used were data from study findings and secondary data from literature, books, questionnaires, and medical records. The sampling technique used in this study was accidental sampling, with a total of 28 samples taken.The results indicated that of the 28 pregnant women examined at the North City Health Center, 1 (3.6%) tested positive for syphilis and 27 (96.4 %) tested negative for syphilis. It can be established that the amount of pregnant women who test positive for syphilis at the North City Health Center was low. This could be attributed to the regularity with which pregnant women visit the Health Center to check on their pregnancy's health and the establishment of a pregnancy health checkup program at the North City Health Center every Wednesday.